Intoleransi Terhadap Pendirian Gereja Non-Muslim dalam Perspektif Moderasi Beragama Di Indonesia - Jazuly Elafi, Muh Sulaiman (Moderatio: Jurnal Moderasi Beragama, 2025)
Religious intolerance toward the construction of churches for non-Muslim communities in Indonesia, especially in Muslim-majority regions, remains a pressing issue despite constitutional guarantees of religious freedom. Repeated cases of rejection, demonstrations, and administrative obstacles illustrate a deeper societal problem rooted in communal pressure and the dominance of majority norms. Analyzing this phenomenon through the perspective of religious moderation an Indonesian framework for promoting tolerance and coexistence offers insight into the social dynamics behind these acts. Using a qualitative descriptive method with a sociological approach, the research draws data from national online media reports including Liputan6, Kompas, Kumparan, and VOA Indonesia, complemented by academic literature on religious pluralism and intergroup relations. Thematic analysis reveals consistent patterns of social resistance, driven by fear of religious minorities, narrow interpretations of religious doctrine, and the politicization of identity. Such resistance contradicts the core principles of religious moderation, which emphasize tolerance, justice, peaceful coexistence, and anti-violence. The findings highlight the importance of promoting inclusive religious understanding through public education, interfaith dialogue, and proactive government policy. Embedding religious moderation in everyday social interactions is vital for ensuring that the rights of religious minorities are respected and that religion continues to serve as a force for compassion, justice, and national unity.